2021
DOI: 10.1002/jcla.23823
|View full text |Cite
|
Sign up to set email alerts
|

Expression of long non‐coding RNA LUCAT1 in patients with chronic obstructive pulmonary disease and its potential functions in regulating cigarette smoke extract‐induced 16HBE cell proliferation and apoptosis

Abstract: Background Chronic obstructive pulmonary disease (COPD), characterized by persistent airflow limitation, was a disease mediated by a combination of inflammatory factors, immune cells, and immune mediators. COPD was an inflammatory and autoimmune disease involving T‐lymphocytes triggered by cigarette smoke and other factors that progressively affected the bronchi, lung parenchyma, and pulmonary blood vessels. LncRNAs were reported to be implicated in COPD pathogenesis and development. Methods Non‐smokers, smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…It has also been shown that the overexpression of LUCAT1 inhibits inducible nitric oxide synthase in lung cells under hyperglycemic conditions [ 46 ]. In line with our study, LUCAT1 was significantly increased in human bronchial epithelial cells following CSE treatment and the knockdown of LUCAT1 in conjunction with CSE treatment led to the alleviation of increased apoptosis and decreased cell proliferation caused by CSE [ 47 ]. Further, Zhao et al demonstrated that these effects are due in part to LUCAT1’s ability to sponge miR-181a, inhibiting miR-181a’s silencing effects on the Wnt/β-catenin pathway [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It has also been shown that the overexpression of LUCAT1 inhibits inducible nitric oxide synthase in lung cells under hyperglycemic conditions [ 46 ]. In line with our study, LUCAT1 was significantly increased in human bronchial epithelial cells following CSE treatment and the knockdown of LUCAT1 in conjunction with CSE treatment led to the alleviation of increased apoptosis and decreased cell proliferation caused by CSE [ 47 ]. Further, Zhao et al demonstrated that these effects are due in part to LUCAT1’s ability to sponge miR-181a, inhibiting miR-181a’s silencing effects on the Wnt/β-catenin pathway [ 47 ].…”
Section: Discussionsupporting
confidence: 84%
“…In line with our study, LUCAT1 was significantly increased in human bronchial epithelial cells following CSE treatment and the knockdown of LUCAT1 in conjunction with CSE treatment led to the alleviation of increased apoptosis and decreased cell proliferation caused by CSE [ 47 ]. Further, Zhao et al demonstrated that these effects are due in part to LUCAT1’s ability to sponge miR-181a, inhibiting miR-181a’s silencing effects on the Wnt/β-catenin pathway [ 47 ]. Altogether, these previous studies suggest an essential role of LUCAT1 in regulating endothelial function.…”
Section: Discussionsupporting
confidence: 84%
“…This implies that upregulation Notch1, which is implicated in various cellular processes such as cell proliferation, differentiation, and apoptosis, stimulates HOXA-AS2dependent cell proliferation and mitigates the cell viability injury. The lung cancer-associated transcript 1 (LUCAT1) is elevated in the serum of COPD patients (Zhao et al, 2021).…”
Section: Chronic Obstructive Pulmonary Disease (Copd)mentioning
confidence: 99%
“…This implies that upregulation Notch1, which is implicated in various cellular processes such as cell proliferation, differentiation, and apoptosis, stimulates HOXA-AS2-dependent cell proliferation and mitigates the cell viability injury. The lung cancer-associated transcript 1 (LUCAT1) is elevated in the serum of COPD patients ( Zhao et al, 2021 ). Further studies in CSE-treated 16HBE cells show that LUCAT1 downregulates its target, miR-181a-5p, upregulates inflammatory cytokines (IL-1β, IL-6, and TNF-α), and regulates cell proliferation and apoptosis via the Wnt/β-catenin pathway ( Zhao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation